Novel inborn error of folate metabolism: identification by exome capture and sequencing of mutations in the MTHFD1 gene in a single proband. Issue 9 (3rd August 2011) - Watkins, David; Schwartzentruber, Jeremy A; Ganesh, Jaya; Orange, Jordan S; Kaplan, Bernard S; Nunez, Laura Dempsey; Majewski, Jacek; Rosenblatt, David S
Abstract : Objective: An infant was investigated because of megaloblastic anaemia, atypical hemolytic uraemic syndrome, severe combined immune deficiency, elevated blood levels of homocysteine and methylmalonic acid, and a selective decreased synthesis of methylcobalamin in cultured fibroblasts. Methods: Exome sequencing was performed on patient genomic DNA. Results: Two mutations were identified in the MTHFD1 gene, which encodes a protein that catalyses three reactions involved in cellular folate metabolism. This protein is essential for the generation of formyltetrahydrofolate and methylenetetrahydrofolate and important for nucleotide and homocysteine metabolism. One mutation (c.727+1G>A) affects the splice acceptor site of intron 8. The second mutation, c.517C>T (p.R173C), changes a critical arginine residue in the NADP-binding site of the protein. Mutations affecting this arginine have previously been shown to affect enzyme activity. Both parents carry a single mutation and an unaffected sibling carries neither mutation. The combination of two mutations in the MTHFRD1 gene, predicted to have severe consequences, in the patient and their absence in the unaffected sibling, supports causality. Conclusion: This patient represents the first case of an inborn error of folate metabolism affecting the trifunctional MTHFD1 protein. This report reinforces the power of exome capture and sequencing for the discovery of novel genes, even when only a single proband is available for study.